Dental anxiety – neglect of dental care - Reddy, R. Sudhakara; Kotha, Ramya; Pavani, K.; Subbarayudu, G.; Rajesh, N.; Sruthi, R. (International Journal of Health, 2015)
Background: The cause of delay in obtaining a dental care definitely depends on the individual’s anxiety status at a dental set up. Anxiety is a state of delirium experienced by an individual. Nevertheless, this feeling of discomfort may hamper the quality of life of an individual.Objectives:To assess the degree of dental anxiety and to assess the reason for dental anxietyMethods: A total of 950 participants were enrolled into the present study. Data was collected using a questionnaire. The questionnaire consisted of two parts; the first part composed of items on demographic characteristics of the patient, and the second part included a questionnaire consisting of combination of Corah’s Dental Anxiety Scale and Dental Fear Survey.Results: In a total sample of 872 patients, 538 individuals were dentally anxious (mean DAS >9) of which 495 patients had a mean score of 9-12 (Mildly anxious); 30 patients had a mean score of 13-15 (Moderately anxious). Only a few subjects (13) were highly anxious (mean DAS > 15). When individual situation of anxiety was assessed, the population noted highest anxiety on feeling or seeing the anaesthetic needle followed by feeling of the vibrations of the drill and being seated in a dental chair.Conclusion: As dental anxiety is a continuum, where to place the cut-off point is a crucial issue in research, which aims to comparesubjects fearful of dentistry with those who are not. The validity of many measures has not been adequately assessed, perhaps because of the difficulty of identifying an external referent against which it may be tested. Evidence in the form of behavioral, physiological orcognitive characteristics should be considered to manage these dentally anxious individuals effectively in the dental office.